Pengaruh Gaya Kepemimpinan Terhadap Kinerja Aparatur Sipil Negara (ASN) Pada Sekretariat Daerah Kabupaten Waropen - Korinus Reri (Pajak dan Manajemen Keuangan, 2025)
This study aims to analyze the relationship between leadership style and the performance of State Civil Apparatus (ASN) in the Waropen Regency Regional Secretariat. Specifically, this study focuses on determining: (1) the strength of the relationship between leadership style and ASN performance, and (2) the level of significance of the relationship between leadership style and ASN performance in the Waropen Regency Regional Secretariat. This study uses an associative or causal research approach to identify the relationship and influence between variables. The study population consists of all ASN in the Waropen Regency Regional Secretariat, totaling 180 people. Sample selection was carried out using the probability sampling method using the cluster sampling technique. Samples were taken from several job groups, namely Regional Secretary Officials, Expert Staff Officials and Assistant Regional Secretaries, sections and subsections, and staff who do not have structural positions. The number of respondents who participated in this study was 60 people. Data collection was carried out through distributing questionnaires and collecting supporting documents. The data used included primary data obtained directly from respondents, as well as secondary data from archives and official documents of related agencies. Data analysis was carried out using correlation analysis techniques to measure the strength of the relationship and significance tests between variables. The results of the study indicate a positive relationship between leadership style and ASN performance, with a correlation coefficient of 0.382, indicating a moderate relationship. Furthermore, a significant positive effect was found with a significance level of 0.003 (<0.05), thus concluding that leadership style significantly contributes to improving ASN performance within the Waropen Regency Regional Secretariat. The implication of this study is the need to strengthen leadership capacity at various levels of office, in order to create a conducive work climate, motivate employees, and encourage optimal performance. These results can be used as a reference for local governments in designing more effective leadership training and development programs.